Business Process Models - Change Management - Gerth, Christian
Driven by the need for a closer alignment of business and IT requirements, the role of business process models in the development of enterprise software systems has increased continuously. Similar to other software artifacts, process models are developed and refined in team environments by several stakeholders, resulting in different versions. These versions need to be merged in order to obtain an integrated process model. Existing solutions to this basic problem in the field of software configuration management are mainly limited to textual documents, e.g., source code. This monograph presents a generally applicable framework for process model change management, which provides easy-to-use comparison and merging capabilities for the integration of different process model versions. The framework supports popular modeling languages such as BPMN, BPEL, or UML Activity Diagrams. Differences between process models are represented in terms of intuitive, high-level change operations. Equipped with a sophisticated analysis of dependencies and a semantic-aware computation of conflicts between differences, the framework constitutes a comprehensive and practically usable solution for process model change management in the model-driven development of enterprise software systems.

How backhaul networks influence the feasibility of coordinated multipoint in cellular networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Kellerer, Wolfgang; Karl, Holger (IEEE Communications Magazine)

Ein pragmatischer Ansatz zur Entwicklung situationsgerechter Entwicklungsmethoden - Spijkerman, Michael (Software Engineering 2013 - Workshopband (inkl. Doktorandensymposium) SE 2013 (to appear))

Kaos4SOA - Extending KAOS Models with Temporal and Logical Dependencies - Nagel , Benjamin; Gerth , Christian; Post, Jennifer; Engels, Gregor (Proceedings of the CAiSE'13 Forum at the 25th International Conference on Advanced Information Systems Engineering (CAiSE'13))

CVSM 2013 Challenge: Recognizing High-level Edit Operations in Evolving Models. - Kehrer , Timo; Gerth, Christian (Proceedings of the Workshop on Comparison and Versioning of Software Models (CVSM'13))

Wiederverwendbarkeit von Migrationswissen durch Techniken der modellgetriebenen Softwareentwicklung - Grieger , Marvin; Sauer, Stefan (Software Engineering 2013 Workshopband)

Goal-driven Composition of Business Process Models - Nagel , Benjamin; Gerth , Christian; Engels, Gregor (Proceedings of the 9th Workshop on Engineering Service-Oriented Applications (WESOA 2013) (accepted for application))

Assembly-based Method Engineering with Method Patterns - Fazal-Baqaie , Masud; Luckey , Markus; Engels, Gregor (Software Engineering 2013 Workshopband)

Instrumentenentwicklung zur Messung von Lernstrategien in mathematikhaltigen Studiengängen - Göller, Robin; Kortemeyer, Jörg; Liebendörfer, Michael; Biehler, Rolf; Hochmuth, Reinhard; Krämer, Jana; Ostsieker, Laura; Schreiber, Stephan (Beiträge zum Mathematikunterricht 2013: Vorträge auf der 47. Tagung für Didaktik der Mathematik)

Mathe – nein danke? Interesse im und am Mathematikstudium bei Grundschullehramtsstudierenden mit Pflichtfach - Kolter, Jana; Liebendörfer, Michael (Mathematik im Übergang Schule / Hochschule und im ersten Studienjahr)

Interest and Self-Determination in the Transition to Studying Mathematics - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 37th Conference of the International Group for the Psychology of Mathematics Education)

Interest in Mathematics and the First Steps at the University - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 8th Conference of European Research in Mathematics Education)

Self-organization of nanospheres in trenches on silicon surfaces - Brassat, Katharina; Assion, Fabian; Hilleringmann, Ulrich; Lindner, Jörg (physica status solidi (a))
The selective deposition and self-assembly of nanospheres from a colloidal suspension in trenches on silicon surfaces is investigated using conventional light, confocal laser scanning and scanning electron microscopy. Trenches with widths of one to several nanosphere diameters are formed on silicon surfaces by photolithography and reactive ion etching. The spreading knife convective self-assembly technique is employed to distribute the nanosphere suspension on the pre-patterned surface. It is shown that this technique is particularly useful in combination with a functionalized surface where a selfassembled molecular monolayer changes the contact angle such that sphere deposition takes place almost exclusively in the trenches. By this, lines selectively filled with a chain of beads with a length of 0.5 mm have been achieved.

Performance and thermal management on self-adaptive hybrid multi-cores - Happe, Markus
Handling run-time dynamics on embedded system-on-chip architectures has become more challenging over the years. On the one hand, the impact of workload and physical dynamics on the system behavior has dramatically increased. On the other hand, embedded architectures have become more complex as they have evolved from single-processor systems over multi-processor systems to hybrid multi-core platforms.Static design-time techniques no longer provide suitable solutions to deal with the run-time dynamics of today's embedded systems. Therefore, system designers have to apply run-time solutions, which have hardly been investigated for hybrid multi-core platforms.In this thesis, we present fundamental work in the new area of run-time management on hybrid multi-core platforms. We propose a novel architecture, a self-adaptive hybrid multi-core system, that combines heterogeneous processors, reconfigurable hardware cores, and monitoring cores on a single chip. Using self-adaptation on thread-level, our hybrid multi-core systems can effectively perform performance and thermal management autonomously at run-time.

On-The-Fly Computing -- Das Entwicklungs- und Betriebsparadigma fürSoftwaresysteme der Zukunft - Engels, Gregor (Proceedings of the Multikonferenz Sofware Engineering 2013 (SE 2013))
Alle Domänen und Branchen der heutigen Wirtschaft sind auf eine effiziente und effektive Entwicklung von benötigten Softwaresystemen angewiesen. Das 40 Jahre alte Prinzip der Beschaffung von Softwaresystemen durch den Einkauf von teuren, relativ unflexiblen Standardlösungen beziehungsweise der noch teureren Erstellung durch Softwarehäuser oder eigene Softwareabteilungen muss deshalb in Frage gestellt werden. Mit dem Einsatz von Cloud Computing-Techniken wird es möglich, Softwaresysteme und die für den Betrieb benötigten Ressourcen nur bei Bedarf und nur in der benötigten Form einzukaufen. Mit dem Ansatz der service-orientierten Architekturen stehen Methoden zur Verfügung, Software zumindest unternehmensintern flexibel zusammenzustellen. Diese ersten Ansätze für eine neue Art der Entwicklung und des Betriebs von Softwaresystemen bilden den Ausgangspunkt für die Forschungen in dem seit 2011 laufenden DFG Sonderforschungsbereich (SFB) 901 „On-The-Fly Computing“ an der Universität Paderborn. Die Vision des On-The-Fly Computing ist, dass die Softwaresysteme der Zukunft aus individuell und automatisch konfigurierten und zur Ausführung gebrachten Softwarebausteinen bestehen, die auf Märkten frei gehandelt werden und flexibel kombinierbar sind. Um zu erforschen, in wie weit diese Vision realisierbar ist, werden Konzepte, Methoden und Techniken entwickelt, die eine weitestgehend automatische Konfiguration, Ausführung und Adaption von Softwaresystemen aus auf weltweiten Märkten verfügbaren Services ermöglichen. Um diese Ziele zu erreichen, arbeiten an der Universität Paderborn Informatiker aus unterschiedlichen Disziplinen wie Softwaretechnik, Algorithmik, Rechnernetze, Systementwurf, Sicherheit und Kryptographie mit Wirtschaftswissenschaftlern zusammen, die ihre spezifische Expertise einbringen, mit der die Organisation und Weiterentwicklung des Marktes vorangetrieben werden kann.

On Two-Party Communication Through Dynamic Networks - Abshoff, Sebastian; Benter, Markus; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Proceedings of the 17th International Conference on Principles of Distributed Systems (OPODIS))
We study two-party communication in the context of directed dynamic networks that are controlled by an adaptive adversary. This adversary is able to change all edges as long as the networks stay strongly-connected in each round. In this work, we establish a relation between counting the total number of nodes in the network and the problem of exchanging tokens between two communication partners which communicate through a dynamic network. We show that the communication problem for a constant fraction of n tokens in a dynamic network with n nodes is at most as hard as counting the number of nodes in a dynamic network with at most 4n+3 nodes. For the proof, we construct a family of directed dynamic networks and apply a lower bound from two-party communication complexity.

On the Quality of Selfish Virtual Topology Reconfiguration in IP-over-WDM Networks - Wette, Philip; Karl, Holger (Proceedings of the 19th IEEE International Workshop on Local and Metropolitan Area Networks (IEEE LANMAN))
The process of planning a virtual topology for a Wavelength Devision Multiplexing (WDM) network is called Virtual Topology Design (VTD). The goal of VTD is to find a virtual topology that supports forwarding the expected traffic without congestion. In networks with fluctuating, high traffic demands, it can happen that no single topology fits all changing traffic demands occurring over a longer time. Thus, during operation, the virtual topology has to be reconfigured. Since modern networks tend to be large, VTD algorithms have to scale well with increasing network size, requiring distributed algorithms. Existing distributed VTD algorithms, however, react too slowly on congestion for the real-time reconfiguration of large networks. We propose Selfish Virtual Topology Reconfiguration (SVTR) as a new algorithm for distributed VTD. It combines reconfiguring the virtual topology and routing through a Software Defined Network (SDN). SVTR is used for online, on-the-fly network reconfiguration. Its integrated routing and WDM reconfiguration keeps connection disruption due to network reconfiguration to a minimum and is able to react very quickly to traffic pattern changes. SVTR works by iteratively adapting the virtual topology to the observed traffic patterns without global traffic information and without future traffic estimations. We evaluated SVTR by simulation and found that it significantly lowers congestion in realistic networks and high load scenarios.

On Greedy Routing in Degree-bounded Graphs over d-Dimensional Internet Coordinate Embeddings - Autenrieth, Marcus; Frey, Hannes (Proceedings of the Conference on Networked Systems (NetSys))
In this paper we will introduce a new d-dimensional graph for constructing geometric application layer overlay net-works. Our approach will use internet coordinates, embedded using the L∞ -metric. After describing the graph structure, we will show how it limits maintenance overhead by bounding each node’s out-degree and how it supports greedy routing using one-hop neighbourhood information in each routing step. We will further show that greedy routing can always compute a path in our graph and we will also prove that in each forwarding step the next hop is closer to the destination than the current node.

MapReduce in Software Defined Networks - Splietker, Malte

Locally Self-Adjusting Tree Networks - Avin, Chen; Häupler, Bernhard; Lotker, Zvi; Scheideler, Christian; Schmid, Stefan (Proceedings of the 27th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
This paper initiates the study of self-adjusting networks (or distributed data structures) whose topologies dynamically adapt to a communication pattern $σ$. We present a fully decentralized self-adjusting solution called SplayNet. A SplayNet is a distributed generalization of the classic splay tree concept. It ensures short paths (which can be found using local-greedy routing) between communication partners while minimizing topological rearrangements. We derive an upper bound for the amortized communication cost of a SplayNet based on empirical entropies of $σ$, and show that SplayNets have several interesting convergence properties. For instance, SplayNets features a provable online optimality under special requests scenarios. We also investigate the optimal static network and prove different lower bounds for the average communication cost based on graph cuts and on the empirical entropy of the communication pattern $σ$. From these lower bounds it follows, e.g., that SplayNets are optimal in scenarios where the requests follow a product distribution as well. Finally, this paper shows that in contrast to the Minimum Linear Arrangement problem which is generally NP-hard, the optimal static tree network can be computed in polynomial time for any guest graph, despite the exponentially large graph family. We complement our formal analysis with a small simulation study on a Facebook graph.